2019
DOI: 10.1111/codi.14635
|View full text |Cite
|
Sign up to set email alerts
|

Anastomotic leak after transanal total mesorectal excision: grading of severity and management aimed at preservation of the anastomosis

Abstract: Aim The transanal approach to total mesorectal excision (TaTME) as an alternative to conventional anterior resection offers an improved view to otherwise restricted anatomical regions in obese and narrow male pelves and unfavourable tumour locations. Guidelines for the management of anastomotic leakage (AL) following low rectal resections are scarce. Patients and methods Prospectively collected data of all consecutive patients undergoing TaTME between December 2014 and April 2017 in our centre were analysed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…Anastomotic failure after the construction of a colorectal anastomosis is associated with significant morbidity and mortality; the risk of permanent stoma after AL is more than 60% and oncologic results, including overall survival, disease-free survival, and cancer-specific survival, are definitively less favorable [18]. In a retrospective analysis, Kang et al identified the overall AL rate after low anterior resection (open and laparoscopic) to be 13.7%, and a higher overall mortality in those cases was also identified in this study [16,19]. According to the most recent publication by the international registry, on 1594 patients, the main risk factors for AL after taTME surgery included male sex, obesity, tumors > 25 mm, excessive intraoperative blood loss, manual anastomosis, and prolonged perineal operative time [17].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Anastomotic failure after the construction of a colorectal anastomosis is associated with significant morbidity and mortality; the risk of permanent stoma after AL is more than 60% and oncologic results, including overall survival, disease-free survival, and cancer-specific survival, are definitively less favorable [18]. In a retrospective analysis, Kang et al identified the overall AL rate after low anterior resection (open and laparoscopic) to be 13.7%, and a higher overall mortality in those cases was also identified in this study [16,19]. According to the most recent publication by the international registry, on 1594 patients, the main risk factors for AL after taTME surgery included male sex, obesity, tumors > 25 mm, excessive intraoperative blood loss, manual anastomosis, and prolonged perineal operative time [17].…”
Section: Introductionsupporting
confidence: 61%
“…Experience and volume seem to have a significant impact on most of the major short-term postoperative outcomes after taTME surgery, including oncologic results and postoperative complications such as anastomotic leak (AL) [14,15]. A persistent concern is the potential marginal increase of AL related to the procedure, which, according to recent literature, could be up to 12-15% overall and close to 8% in the 30 days following surgery [16,17]. Anastomotic failure after the construction of a colorectal anastomosis is associated with significant morbidity and mortality; the risk of permanent stoma after AL is more than 60% and oncologic results, including overall survival, disease-free survival, and cancer-specific survival, are definitively less favorable [18].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis 28 that involved 899 patients also showed no significant differences in overall postoperative complications (p = .39) and AL (p = .60). In another retrospective study by Guel-Klein et al, 29 eight episodes of AL among 66 patients were reported, and the overall incidence of AL was 12.1%, which is comparable with the results of laTME. Most studies concluded that taTME would not lead to a higher rate of postoperative complications and confirmed the noninferiority of its short-term outcomes.…”
Section: Postoperative Complications and Anastomotic Leakagesupporting
confidence: 63%
“…While eAL could be treated only with endosponge therapy, lAL required a multimodal approach consisting of endosponge therapy, transanal suture and reopening of diverting loop-ileostomy. Our therapeutic approach relies on our experiences after TaTME for rectal carcinoma, where we developed a differentiated therapy strategy for AL (20). Endosponge therapy for AL after IPAA has not yet been widely researched, but the few studies existing show non-inferiority in comparison to conventional treatment and high rates of pouch preservation (21,29).…”
Section: Discussionmentioning
confidence: 99%
“…The multimodal treatment procedures of AL management include -depending on the extent of ALantibiotic therapy, radiological or endoscopic interventions as well as reoperation with the intend to preserve continuity, as recently shown by different groups for AL for rectal cancer and in ammatory bowel disease (19)(20)(21).…”
Section: Read Full License Introductionmentioning
confidence: 99%